Menstrual Dysfunction in Adolescent Female Athletes - Valeria Calcaterra; Matteo Vandoni; Alice Bianchi; Agnese Pirazzi; Lara Tiranini; Paola Baldassarre; Marianna Diotti; Caterina Cavallo; Rossella Elena Nappi; Gianvincenzo Zuccotti (Sports, 2024)
Despite the benefits of exercise on mental and physical health, excessive training loads can lead to health problems in the long term, including a wide spectrum of menstrual dysfunction (MD). This narrative review aims to analyze the relationship between physical exercise and MD in adolescent female athletes to support regular menstrual health monitoring and promote educational programs on reproductive risks. When dealing with MD in young athletes, several factors entangled with maturation of the hypothalamus–pituitary–ovarian axis should be considered. Firstly, some disciplines seem to have a higher prevalence of MD due to the high loads of training regimes and the early introduction of athletes to a competitive career. Moreover, low energy intake and a low body mass index appear to exacerbate existing MD. Lastly, disordered eating behaviors and psychological stress can contribute to MD in female athletes. The type of sport, influencing the intensity and duration of exercise, as well as individual psycho-physiological and environmental factors, may influence the role of physical activity in the manifestation of MD. Early recognition and management of MD, along with collaboration between sports organizations and health professionals, are crucial to minimize risks, ensure proper nutrition, and balance training with recovery. Keeping an open discussion on the topic may prospectively improve awareness, early diagnosis, and treatment strategies, as well as reduce injury risk and enhance sports performance.